Review on Forensic Chemistry: Importance in Identify-ing Unidentified Bodies and Mass Graves and Missing Persons: Perancangan Model Pengembangan Pariwisata Perkotaan yang Berkelanjutan untuk Karbala didasarkan pada Aspek Sosial, Budaya, dan Keagamaan Kota Karbala - Al-Banaa, Marwah A. Kadhim; Mohammed, Baraa Kasim (Academia Open, 2026)
General Background: Forensic chemistry plays a crucial role in criminal investigations by analyzing non-biological evidence and supporting identification processes. Specific Background: In cases involving mass graves and missing persons, forensic chemistry works alongside forensic anthropology to identify skeletal remains and reconstruct events. Knowledge Gap: Despite growing attention, there is limited integrated understanding of how forensic chemistry techniques support identification in complex mass grave contexts. Aims: This study reviews the role of forensic chemistry in identifying unknown bodies and analyzing mass grave evidence. Results: The findings highlight that forensic investigations rely on evidence collection, skeletal analysis, age estimation methods, and advanced imaging technologies to support identification processes. Novelty: The study integrates forensic chemistry principles with anthropological and technological approaches in the context of mass grave investigations. Implications: The results emphasize the importance of multidisciplinary approaches and technological advancements to support accurate identification and provide answers for affected families. Keywords: Forensic Chemistry, Mass Graves, Skeletal Identification, Forensic Anthropology, Crime Scene Analysis Key Findings Highlights Evidence collection procedures form the basis of identification processes Advanced imaging supports detailed skeletal examination Multidisciplinary collaboration strengthens investigative outcomes